Children’s Critical Thinking Skills Developing in Learning of Foreign Languages - Trusov I. E. (Pedagogy and Psychology as a Source of Development of Modern Society, 2021)
the article is devoted to the problem of developing critical thinking skills in teaching foreign languages. Some differences are considered both in teaching a foreign language in general education schools and in private ones. The role of parents in teaching their children is also considered.
Keywords: критическое мышление; critical thinking; учительская компетентность; роль родителей в образовании; teaching competence; the role of parents in education